EXPRESSION OF DIVERSITY IN TAHLILAN: An Interfaith Study of the Death Rites in Muntilan Magelang and Babadan Sleman Yogyakarta - Fathorrohman (Universitas Islam Negeri (UIN) Mataram, 2022)
This paper describes interfaith tahlilan that occurred in two areas, namely Ngawen, Muntilan, Magelang and Babadan, Sleman, Yogyakarta. As a death rite, interfaith tahlilan is held by Catholics at their homes to pray for their families who have died. By involving various levels of society in Ngawen and Babadan, both Muslim and Catholic, this interfaith tahlilan was led by Islamic leaders in the two areas. In the process, interfaith tahlilan is accepted as a form of religious accommodation by Muslims, but on the other hand it becomes a separate discourse whether tahlilan to pray for Catholics is commonly carried out and can be granted by Allah. To find out the portrait of the dynamics of cross-faith tahlilan, there are three basic questions posed in this paper, namely, first, what is meant by interfaith tahlilan? Why is interfaith tahlilan carried out by Catholics and involves Muslims? How is the discursive space carried out by Muslim actors so that interfaith tahlilan can be carried out? To analyze the three questions, the author uses the anthropological theory of death and traditional discourse to describe the facts that occur in the field. Therefore, to find out the facts on the ground, methodologically the author uses interviews with key figures and conducts Focus Group Discussions to obtain broad views from the residents of Ngawen Magelang and Babadan Yogyakarta. From the results of our study, the authors argue that tahlilan carried out by the Ngawen and Babadan peoples is motivated by an awareness of inclusiveness in carrying out religious practices in the midst of diversity while at the same time promoting the spirit of citizenship as an anthropological building in society.